Answer:
No does not contain the same length
Step-by-step explanation:
Given that
A(-4,2) , B (1,4), C (2, -1)
Now
AB would be
= [tex]\sqrt{(1-(-4))^2 + (4-2)^2} \\\\= \sqrt{29}[/tex]
And, BC is
[tex]= \sqrt{(2-1)^2 + 1-(-4))^2} \\\\= \sqrt{26}[/tex]
As we can see that the AB and BC are not equaled
So,
AB ≠ BC
Due to the different length
Therefore they do not contains the same length
We simply applied the distance formula due to which the length could be determined and the same is to be considered